KORUPSI, KOLUSI DAN NEPOTISME PERSPEKTIF HADITS - Teguh Luhuringbudi; Achmad Yani (IAIN Manado, 2018)
Abstract. This study concludes that the rise of corruption, collusion, and nepotism in the time of the Prophet Muḥammad comes from a variety of special terms and is contained in ḥadīth. These emerging terms affect the different usage associations of each term. The method used in this research is analytical and descriptive method. This study uses two approaches. The first approach used in the research is the 'ilm al-Ḥadīth approach. This approach is used to measure ḥadīth-ḥadīth relating to corruption, collusion and nepotism in terms of quality of matan and sanad; and its asbāb al-Wurūd. The second approach is the linguistic approach. This approach is enabled to explore the rationality of corruption, collusion, and nepotism through tradition, systematics, and language tendencies in producing an understanding. This research has several objectives. Firstly, to authenticate corruption, collusion, and nepotism as disciplinary and inconsistent attitudes that can be present in human beings without being limited by the dimension of time and space. Secondly, to verify and measure the existence of cases of corruption, collusion, and nepotism in the time of Mu'ammad ibn 'Abdillāh by analyzing the matan al-Ḥadīth, Sharh al-Ḥadīth, and asbāb al-Wurūd. Thirdly, inventory the terms of corruption, collusion, and nepotism in ḥadīth and map their usage.Keywords: Corruption, Collusion, Nepotism, and ḤadīthAbstrak. Penelitian ini menyimpukan bahwa maraknya karupsi, kolusi, dan nepotisme pada masa nabi Muḥammad hadir dari istilah khusus yang beragam dan terdapat dalam ḥadīth. Istilah-istilah yang muncul tersebut berdampak pada asosiasi penggunaan yang berbeda dari masing-masing istilahnya. Metode yang digunakan dalam penelitian ini adalah metode analitis dan deskriptif. Penelitian ini menggunakan dua pendekatan. Pendekatan pertama yang digunakan dalam penelitian adalah pendekatan ‘ilm al-Ḥadīth. Pendekatan ini difungsikan untuk menakar ḥadīth-ḥadīth yang berkaitan dengan korupsi, kolusi, dan nepotisme secara kualitas matan dan sanadnya; dan asbāb al-Wurūd nya. Pendekatan kedua adalah pendekatan kebahasaan. Pendekatan ini difungsikan untuk menelusuri rasionalitas terjadinya korupsi, kolusi, dan nepotisme melalui tradisi, sistematika, dan kecenderungan kebahasaan dalam memproduksi suatu pemahaman. Penelitian ini memiliki beberapa tujuan. Pertama, mengobjektifikasi korupsi, kolusi, dan nepotisme sebagai sikap indisipliner dan inkonsisten yang dapat hadir dalam diri manusia tanpa dibatasi dimensi waktu dan ruang. Kedua, memastikan dan mengukur keberadaan kasus korupsi, kolusi, dan nepotisme pada masa Muḥammad ibn ‘Abdillāh dengan menganalisis matan al-Ḥadīth, Sharh al-Ḥadīth, dan asbāb al-Wurūd. Ketiga, menginventarisir istilah-istilah korupsi, kolusi, dan nepotisme dalam ḥadīth dan memetakan penggunaannya. Kata Kunci: Korupsi, Kolusi, Nepotisme, dan Ḥadīth